A Mixed-Methods Study of ED and NED Students' LMS Experience in English Language Learning - Adelia Aprilliani Puteri; Putu Dian Danayanti Degeng (Journal of English Language Teaching and Linguistics, 2026)
This study examines the differences in the experiences of English Department (ED) and non-English Department (NED) students in using a Learning Management System (LMS) for English language learning (ELL) and investigates how LMS use contributes to the improvement of English language skills in ED and NED students. Using a mixed-method approach based on explanatory-sequential design, this study involved 185 students from Brawijaya University. The research began with quantitative data collection through a Likert scale questionnaire, followed by qualitative data collection through semi-structured interviews with seven students. This study showed that, although ED and NED students have excellent technological skills in using LMS, their application to English language skill development is uneven. Reading, writing, and listening skills show significant improvement, but speaking skills did not develop rapidly across all students. The results revealed that the differences in LMS usage experiences were not due to differences in major but were caused by limitations in the learning design of the LMS, particularly its inability to adequately support speaking practice. To address this gap, educators need to integrate synchronous communication tools and interactive speaking activities into the LMS. This will create a more balanced and comprehensive English learning experience through pedagogical innovation and appropriate use of technology.